Physiological demands of simulated off-road cycling competition - Smekal, G.; von Duvillard, S. P.; Hörmandinger, M.; Moll, R.; Heller, M.; Pokan, R.; Bacharach, D. W.; LeMura, L. M.; Arciero, P. (Journal of Sports Science & Medicine, 2015)
The purpose of the study was to measure the demands of off-road cycling via portable spirometry, leg-power output (PO), heart rate (HR) and blood lactate (BLa) concentration. Twenty-four male competitive cyclists (age: 29±7.2 yrs, height: 1.79 ± 0.05 m, body mass: 70.0 ± 4.9 kg, VO2peak: 64.9 ± 7.5 ml·kg-1·min-1) performed simulated mountain bike competitions (COMP) and laboratory tests (LabT). From LabT, we determined maximal workload and first and second ventilatory thresholds (VT1, VT2). A high-performance athlete (HPA) was used for comparison with three groups of subjects with different sport-specific performance levels. Load profiles of COMP were also investigated during uphill, flat and downhill cycling. During the COMP, athletes achieved a mean oxygen uptake (VO2COMP) of 57.0 ± 6.8 ml·kg-1·min-1 vs. 71.1 ml·kg-1·min-1 for the HPA. The POCOMP was 2.66±0.43 W·kg-1 and 3.52 W·kg-1 for the HPA. POCOMP, VO2COMP and HRCOMP were compared to corresponding variables at the VT2 of LabT. LabT variables correlated with racing time (RTCOMP) and POCOMP (p < 0.01 to <0.001; r-0.59 to -0.80). The VO2peak (LabT) accounted for 65% of variance of a single COMP test. VO2COMP, POCOMP and also endurance variables measured from LabTs were found as important determinants for cross-country performance. The high average VO2COMP indicates that a high aerobic capacity is a prerequisite for successful COMP. Findings derived from respiratory gas measures during COMPs might be useful when designing mountain bike specific training.